Penerapan Sketchup dalam Perhitungan Rencana Anggaran Biaya sebagai Pendekatan BIM pada Pembangunan Rumah Tipe 45 - Qodiron, Lailatul; Oktarina, Devi; Fadilasari, Dewi (Universitas Ibn Khaldun, 2023)
Nowadays, the Building Information Modeling (BIM) method is still a hot topic in the world of construction. However, the use of the BIM method has only been used by large projects in Indonesia. In this study, the use of the BIM approach method was applied to the Type 45 House Development Project in Teluk Betung, Bandar Lampung City. This research aims to calculate the Budget Plan (RAB) using Sketchup with the help of the Quantifier Pro extension. The results obtained in this study are in the form of 3-dimensional image modeling using Sketchup, recapitulating the amount of the budget, and making a project schedule. This study concludes that the total cost calculation obtained using the Sketchup Quantifier Pro extension is Rp. 192,228,579 with the time needed for 16 weeks.